Réponses

2013-06-10T22:01:39+02:00

fct affine donc de la forme f(x)=ax+b

 

f1(1)=4  et f1(4)=7

donc

4=a+b

7=4a+b

d'ou 3=3a donc a=1 d'ou b=3 donc f1(x)=x+3

 

f2(2)= -1 et f2( -1)=2  

donc

-1=2a+b

2=-a+b

d'ou -3=3a d'ou a=-1 et b =1 donc f2(x)=-x+1

 

 

Meilleure réponse !
  • Utilisateur Brainly
2013-06-10T22:02:33+02:00

a) f1(x)=ax+b

f1(1)=4 donc a+b=4

f1(4)=7   donc 4a+b=7

donc 3a=3 donc a=1

donc b=3

donc f1(x)=x+3

 

b) f2(x)=ax+b

f2(2)= -1 donc 2a+b=-1

f2( -1)=2  donc -a+b=2

donc 3a=-3 donc a=-1

donc b=1

donc f2(x)=-x+1